Information rights in practice : the non-legal professional's guide / Alan Stead. - Stead, Alan (Facet, 2008)
Overstretched professionals in every public authority are grappling with the chalk face implications of a raft of legislation relating to information use. This is the first book to offer a single point of reference and advice, which can be understood by the non-legal professional. The requirements of the relevant legislation are set out together with examples, flow-charts, and diagrams to illustrate and clarify how to apply the law in practice. This indispensable guide is a one-stop shop for all you need to know about information rights law, using relevant case studies to clarify and illuminate these tricky issues. Contents include: Data Protection Act 1998 - definitions of personal data; scope of the Act; the principles; access to personal data and data sharing; and, Freedom of Information Act 2000 and the Environmental Information Regulations 2004 - scope of the Acts; applications of exemptions/exceptions; public interest tests, publication schemes; and, disclosure logs and records management. It also includes: Regulation of Investigatory Powers Act 2000; Human Rights Act 1998; Re-use of Public Sector Information Regulations 2005; other non-information rights-related legislation; interaction of legislation; and, requests for information. A must-have for anyone working with information rights in public authorities and the private sector, this book is also a useful reference point for legal advisers, academics and students of information rights, as well as media professionals wanting to learn and understand how public authorities approach requests for information and the surrounding procedures.